اليات دعم و ترقية التشغيل في الجزائر دراسة حالة الصندوق الوطني للتأمين عن البطالة - محمد فيصل ،دندوقي; أحمد أمير ،شريف (جامعة الوادي University of El Oued, 2024)
هدفت هذه الدراسة إلى الوقوف على أهم الآليات المؤسساتية للتشغيل المستحدثة في الجزائر، والتركيز على تحليل وتقييم دور الصندوق الوطني للتأمين عن البطالة في دعم وترقية التشغيل من خلال دراسة مضامين الأجهزة الثلاثة المشكلة له بالشرح والتفصيل، وتقييم نتائج هذه الأجهزة لمعرفة مدى فعالية هذا الأجهزة في تحقيق أهدافها التي أنشِئت من أجلها، ولقد أظهرت النتائج كافة الجهود المبذولة من الدولة فيما يتعلق بتنويع وتنظيم وتطوير آليات التشغيل بما يتناسب مع مختلف الشرائح البطالين، كما أبرزت الدراسة دور الصندوق الوطني للتامين عن البطالة من خلال أجهزته الثلاثة، باعتباره آلية مهمة من آليات دعم ترقية التشغيل في الجزائر، لما حققه من نتائج ملموسة على أرض الواقع، في دعم وترقية التشغيل، والحد من تفاقم ظاهرة البطالة. This study aimed to identify the most important institutional mechanisms for employment developed in Algeria, and to focus on analyzing and evaluating the role of the National Unemployment Insurance Fund in supporting and promoting employment by studying the contents of the three devices formed for it in explanation and detail, and evaluating the results of these devices to determine the extent of the effectiveness of these devices. In achieving its goals for which it was established. The results showed all the efforts made by the state with regard to diversifying, organizing and developing employment mechanisms in a way that suits the various segments of the unemployed. The study also highlighted the role of the National Unemployment Insurance Fund through its three agencies as an important mechanism for supporting the promotion of employment in Algeria, due to its achievements. Tangible results on the ground, in supporting and promoting employment, and reducing the aggravation of the unemployment phenomenon.
ماستر سياسة عامة